Spanish - Lopez Sanchez, Maria Engraciada; Nissler, Dominique ([Hauppauge, N.Y.] Barron's Educational, 2006)
A practical, quick, and convenient way to communicate in various situations in Spanish. 0
CD 1. Lessons 1-8 and review 1 -- CD 2. Lessons 9-16 and reviews 2,3, & 4 -- CD 3. Vocabulary coach -- CD 4. Take along CD.
Texts by Maria Engracia Lopez Sanchez in collaboration with Dominique Nissler.
Compact disc.
English and Spanish.
Keywords: Spanish language -- Textbooks for foreign speakers -- English; Spanish language -- Sound recordings for foreign speakers -- English; Spanish language -- Audio-visual aids; Spanish language materials -- Bilingual